2018
DOI: 10.1371/journal.pone.0193303
|View full text |Cite
|
Sign up to set email alerts
|

Does dexmedetomidine have an antiarrhythmic effect on cardiac patients? A meta-analysis of randomized controlled trials

Abstract: BackgroundCardiac surgery patients often experience several types of tachyarrhythmias after admission to the intensive care unit (ICU), which increases mortality and morbidity. Dexmedetomidine (DEX) is a popular medicine used for sedation in the ICU, and its other pharmacological characteristics are gradually being uncovered.PurposeTo determine whether DEX has an antiarrhythmic effect after cardiac surgery.MethodsThe three primary databases MEDLINE, Embase (OVID SP) and the Cochrane Central Register of Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
11
0
3
Order By: Relevance
“…Previous systematic reviews and meta-analysis [20,42] found that DEX did not affect AF incidence after cardiac surgery. However, Liu et al [43] indicated that DEX could reduce the incidence of AF and VT after cardiac surgery but has no effect on VF incidence (this result was consistent with our research results).…”
Section: Discussionmentioning
confidence: 90%
“…Previous systematic reviews and meta-analysis [20,42] found that DEX did not affect AF incidence after cardiac surgery. However, Liu et al [43] indicated that DEX could reduce the incidence of AF and VT after cardiac surgery but has no effect on VF incidence (this result was consistent with our research results).…”
Section: Discussionmentioning
confidence: 90%
“…An additional advantage of dexmedetomidine over physostigmine is its lower arrhythmogenic potential [18][19][20]. It is safe and may even be protective, in the setting of prolonged QTc [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest report by National Poison Data Systems, there are more than 40,000 exposures to antihistamines in children with exposures growing by over 1,000 every year over the last ten years. In 2018, antihistamines were found to be the second most common cause of pharmaceutical death in ages [13][14][15][16][17][18][19]. This is in addition to other medications that cause anticholinergic presentations such as antipsychotics and nonpharmaceutical exposures [1].…”
Section: Introductionmentioning
confidence: 99%
“…32 A meta-analysis including 1295 patients in 9 studies concluded that dexmedetomidine is associated with a lower incidence of ventricular arrhythmia after elective cardiac surgery. 33 Methohexital minimizes the possibility of potentially life-threatening cardiac arrhythmias during electroconvulsive therapy compared with thiamylal or thiopental. 34 In contrast, midazolam, which does not suppress SKNA, does not alter the inducibility of reentrant tachycardia nor has it be shown to affect the sinoatrial node, refractory periods of atrioventricular conduction, or accessory pathways.…”
Section: Antiarrhythmic Effects Of Anesthesia Agentsmentioning
confidence: 99%